2018
DOI: 10.3390/polym10101142
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of Plasticizing Effect on Bio-Based Polyurethane Acrylate Solid Polymer Electrolyte and Its Properties

Abstract: Polyurethane acrylate (PUA) from vegetable oil has been synthesized and prepared for solid polymer electrolyte. Polyol has been end-capped with Toluene 2,4-Diisocyanate (TDI) followed by hydroxylethylmethylacrylate (HEMA) in a urethanation process to produce PUA. The mixtures were cured to make thin polymeric films under UV radiation to produce excellent cured films which exhibit good thermal stability and obtain high ionic conductivity value. 3 to 15 wt. % of ethylene carbonate (EC) mixed with 25 wt. % LiClO4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…Currently, palm oil is one of the common vegetable oils used to produce polyol that can be applied as a PU paint resin with two-component systems that are suitable for both interior and exterior applications [ 11 ]. Jatropha oil is still new as a raw material for synthesizing polyol in Malaysia and only a few studies have reported on the use of jatropha oil for PU production for different applications so far, mainly studied by our group [ 12 , 13 , 14 , 15 , 16 ]. The usage of non-edible jatropha oil is a new alternative to reduce the dependency on edible oil for polymer production.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, palm oil is one of the common vegetable oils used to produce polyol that can be applied as a PU paint resin with two-component systems that are suitable for both interior and exterior applications [ 11 ]. Jatropha oil is still new as a raw material for synthesizing polyol in Malaysia and only a few studies have reported on the use of jatropha oil for PU production for different applications so far, mainly studied by our group [ 12 , 13 , 14 , 15 , 16 ]. The usage of non-edible jatropha oil is a new alternative to reduce the dependency on edible oil for polymer production.…”
Section: Introductionmentioning
confidence: 99%
“…EC was selected for this study because of its high dielectric constant and low vapor pressure. With the addition of EC, it was envisaged that many charge carriers would localize along with the mobile ions, thereby improving the SPE’s ionic conductivity [ 67 ]. As expected, the DSC thermogram of MPK15 showed a significant decrease in the T g value (9.08 °C).…”
Section: Resultsmentioning
confidence: 99%
“…Various electro-spun fibrous PU separators, such as PU/Al 2 O 3 [29], PU/graphene oxide (GO) [30], and PU/Poly(vinylidene fluoride) (PVDF) [31], have been reported. In addition, PU has been modified by blending [32], crosslinking [33], and plasticizers [34], showing its potential as a polymer electrolyte. Despite their excellent stretch properties, the electrospinning method has drawbacks, including optimization of separator properties (porosity and pore size), sensitivity to the manufacturing environment (temperature and humidity), and a slow production rate [35].…”
Section: Introductionmentioning
confidence: 99%